Factors Influencing Rehospitalisation of Patients with Schizophrenia in Japan: A 1-year Longitudinal Study. Issue 1 (December 2016) - Shimada, Takeshi; Nishi, Ai; Yoshida, Tomotaka; Tanaka, Sachie; Kobayashi, Masayoshi
Objective/Background: This longitudinal study explored factors influencing the rehospitalisation of patients with schizophrenia in Japan. Methods: Participants comprised patients with schizophrenia who were discharged from a psychiatric hospital in Japan. The investigations were conducted at the time of discharge and one year later. Demographics and clinical characteristics included the following: the type of occupational therapy (OT) interventions (group and individualized or group only); the assessment scales' scores on hospitalisation; the community living conditions after discharge; and the contents of outpatient treatment (outpatient OT, day-care treatment, home-visit nursing, and adherence to outpatient treatment and medication). All variables were examined in a binomial logistic regression analysis to identify the factors for rehospitalisation. Results: The rehospitalisation rate was 31.8%, as 14 of 44 participants were rehospitalised within one year after discharge. The type of OT interventions (OR = 7.05, 95% CI = 1.36 −36.69, p = .020) and the adherence to outpatient treatment and medication (OR = 9.48, 95% CI = 1.82–49.33, p = .008) were significant contributing factors to rehospitalisation. Conclusion: This study provided preliminary support for the finding that individualized occupational therapy and proper adherence to outpatient treatment and medication are associated with reducing the rehospitalisation of patients with schizophrenia in Japan.